2021
DOI: 10.1108/ijccsm-06-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of renewable energy consumption to CO2 emissions mitigation: a comparative analysis from the income levels’ perspective in the belt and road initiative (BRI) region

Abstract: Purpose This paper aims to retrospectively quantify the contribution of renewable energy consumption (REC) to mitigate the carbon dioxide (CO2) emissions for the belt and road initiative (BRI) region. The reason is that, so far, still few scientists have deeply analyzed this underlying impact, especially from the income levels’ perspective. Design/methodology/approach The study divides the BRI region into four groups by the income levels (high, HI; upper middle, UM; lower middle, LM; lower, LO) during 1992–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Because companies often are allowed favourable exemptions for existing infrastructure, inefficient insulated structures continue to be used without being replaced. These findings confirm other studies where many countries have focused overly on renewable sources and not the science and technology for saving energy (Jia et al , 2021a); this strategy has been found inadequate for achieving reductions (Jia et al , 2021b). It would appear that many environmental managers know what good environmental decisions are but are prevented from making them due to short timelines used to justify cost and profit requirements.…”
Section: Resultssupporting
confidence: 88%
“…Because companies often are allowed favourable exemptions for existing infrastructure, inefficient insulated structures continue to be used without being replaced. These findings confirm other studies where many countries have focused overly on renewable sources and not the science and technology for saving energy (Jia et al , 2021a); this strategy has been found inadequate for achieving reductions (Jia et al , 2021b). It would appear that many environmental managers know what good environmental decisions are but are prevented from making them due to short timelines used to justify cost and profit requirements.…”
Section: Resultssupporting
confidence: 88%
“…The optimization of power structure requires the coordinated development of electricity with energy, economy, environment and other factors. It is very important to develop and use clean energy (Jia et al, 2021). Therefore, the higher the proportion of clean energy in power generation, the higher the energy efficiency will be.…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…As shown in Columns ( 4) and (5) of Table 5, carbon trading policy is more effective in improving energy efficiency for high level power structures, which will be more responsive to carbon trading policy because of their weaker lock-in and inertia effects, while the opposite is true for low-level power structures. The optimization of power structure requires the coordinated development of electricity with energy, economy, environment and other (Jia et al, 2021). Therefore, the higher the proportion of clean energy in power generation, the higher the energy efficiency will be.…”
Section: Heterogeneity Analysismentioning
confidence: 99%
“…Moreover, while energy transition is favourable for sustainable development, particularly in the environmental aspect (Bilgili et al, 2016;Chen et al, 2019;Dong et al, 2020;Jia et al, 2021;Mukhtarov et al, 2022;Nathaniel & Iheonu, 2019;Ummalla & Samal, 2019), its impact also needs to be assessed from economic and social perspectives. Studies by Ferrari & Landi (2022) show that energy transition increases inflation in the European region.…”
Section: Introductionmentioning
confidence: 99%